SAT0033 Characterization of the Multi-Biomarker Disease Activity (Vectra Da™ Algorithm) Score in a Subgroup of Patients from the Epidemiological Investigation of Rheumatoid Arthritis (EIRA) Cohort Receiving Methotrexate. (23rd January 2014) - Li, W.; Hensvold, A. H.; Saevarsdottir, S.; Defranoux, N. A.; Klareskog, L.; Catrina, A. I.
Abstract : Background: A multi-biomarker disease activity (MBDA) score has been shown to reflect disease activity at the molecular level in patients with rheumatoid arthritis (RA). The use of MBDA or its components to predict methotrexate (MTX) response has yet to be determined. Objectives: To characterize the MBDA score in RA patients treated with MTX and its ability to predict treatment response. Methods: The Epidemiological Investigation of Rheumatoid Arthritis (EIRA) cohort includes patients diagnosed with RA and symptom disease duration < 1 year. This study was conducted on a subgroup of 186 EIRA subjects from the Karolinska University Hospital who were naïve to disease modifying anti-rheumatic drug and were started on MTX monotherapy at study entry. Clinical disease activity and serum biomarker concentrations were measured at baseline (BL) and 3 months. Concentrations of VCAM-1, EGF, VEGF-A, IL-6, TNF-RI, YKL-40, MMP-1, MMP-3, leptin, resistin, SAA and CRP were integrated to derive a MBDA score (range 1-100) using a previously validated algorithm [1 ]. Anti-CCP was measured by ELISA at BL. Spearman's rank correlation was used to determine correlations between the clinical disease activity scores and the individual biomarker concentrations or the MBDA Score. Response to treatment at 3 months was assessed using the EULAR criteria. MBDA stratification of EULAR good- and moderate- responders vs. non-responders was evaluated with area under receiver operating characteristic curves (AUROCs). No correction for multiple testing was done when analyzing the single biomarkers. Results: Patient baseline characteristics (n=186) were similar to those of the original large EIRA cohort with median (IQR) age 52(42-59), 72% female, 67% anti-CCP positive. At baseline the median (IQR) DAS28-ESR was 5.7 (5.0-6.2) and MBDA score was 58 (47-66). 29% of the patients were good EULAR responders, 37% moderate and 34% non-responders. When analyzing patient baseline characteristics anti-CCP negativity and male sex were associated with EULAR response to MTX treatment at 3 months, whereas BL MBDA score and BL concentrations of individual biomarkers were not. The median changes in MBDA score from BL to 3 months were (-16) for good responders, (-12) for moderate and (+2) for non-responders. Changes in MBDA scores and in concentrations of single biomarkers differentiated responders from non-responders at 3 months (MBDA Score: AUROC = 0.79, p-value <0.001). The changes in MBDA score and in concentration of biomarkers were significantly correlated with changes in DAS28-ESR (MBDA Score: r = 0.60, p <0.001). A sub-analysis to compare the behavior of MBDA score in patients with different anti-CCP status showed no significant difference in the AUROC for the changes in MBDA score when discriminating responders from non-responders (AUROC=0.76 vs. 0.84 for ACPA (+) vs. (-) group; p>0.05). Conclusions: MBDA and its biomarker components can track and differentiate the clinical response in early RA patients treated with MTX, regardless of anti-CCP status. References: Curtis JR, et al., Validation of a novel multi-biomarker test to assess rheumatoid arthritis disease activity. Arthritis Care & Research 2012 Dec; 64(12):1794-803. Disclosure of Interest: W. Li Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, A. Hensvold : None Declared, S. Saevarsdottir: None Declared, N. Defranoux Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, L. Klareskog: None Declared, A. Catrina : None Declared